BUSINESS-TO-BUSINESS CORRUPTION - Natasha Georgieva Hadzi Krsteski (Journal of Process Management and New Technologies, 2016)
The business corruption is established and active in the circle of the businesses partners that express a gratitude, return a service or bribes (apart from ordinary price) for a business transfer to be provided. Those prohibited transfers differs from the usual business transfers, such as activities related to marketing and public relations where they have a specific goal to use illegal means in order to infringe the recipients` identity of prohibited value in an interchange for a inducement. That is a procedure of enticement, which prevents the useful instruments in the permitted bazaar and not solitary that it is harmful for the businesses whose representatives accept bribe, however it is also harmful for the civilisation as an entire. The occurrence of business corruption is intended as a amount of companies that presented cash, a gratitude or a service in return, in adding to every usual deal of any person who is working for a business entity from the private sector in any capacity, including the one through a mediator, happening to at minimum single juncture in the past 12 months previous to this research. The usual commonness of the business-to-corruption in the Republic of Macedonia is 3% compared to 4% at a regional level). While it is fewer than the regular pervasiveness of salaried briberies by enterprises to civic bureaucrats, this discovery designates that bribery in the secluded segment is a difficult in the Republic of Macedonia.